Application of Pressure-Sensitive Materials in Cement-Based Composites for Self-Assessment of Structural Degradation - Cheng, An (Asian Journal of Chemistry, 2014)
The accumulation of internal defects in materials often results in degraded performance and the prevention of sudden material failure has become an important issue in materials research. In large structures such as buildings and bridges, sudden collapses due to the buildup of internal cracks can lead to significant losses, both in property and lives. If concrete structures were capable of performing self-assessments to reveal the presence of cracking, warnings could be issued before actual damage occurs. The addition of conductive materials is necessary to perform this kind of self-diagnosis in cement-based materials. This study added graphite to cement-based materials to investigate conductivity behavior and sensitivity to the effects of pressure. This study was conducted the mixture with a water-cementitious ratio of 0.6 for the preparation of cylindrical specimens (j 10 cm × 20 cm) in which 5, 10 and 15 % of the cement was replaced with graphite. We then investigated the influence of graphite contents on the electrical resistivity of the mortar and conducted cyclic loading tests to determine the relationship between rate of change in resistivity, stress and strain, and the application of load and the resulting changes in resistivity to indicate the existence and development of internal cracking. Results show that the addition of graphite to mortar significantly reduces the compressive strength of the concrete presented a linear decline proportional to the addition of graphite. With regard to resistivity, concrete with 5 % graphite content reached the percolation threshold of the concrete and with an increase in the amount of graphite, resistivity gradually decreased. In cyclic loading tests with a fixed load, specimens with 5 % or more graphite content were better able to reflect the relationship between loading and resistivity. The results of cyclic loading tests with loads of increasing and decreasing magnitude indicated that specimens with 10 and 15 % graphite content provided a clearer indication of the relationship between loading and resistivity, due to their increased sensitivity to internal cracking conditions. In this study, the mixture in which 10 % of the cement was replaced by graphite provided the best tradeoff between strength and sensitivity to the effects of cracking, making it the best option for practical use in construction.